LE B-LEARNING COMME UNE MODALITÉ D’APPRENTISSAGE COMPLÉMENTAIRE DANS L’ATELIER DE CRÉATIVITÉ - Blachowska-Szmigiel, Marzena; Pacholczyk, Séverine (Neofilolog, 2019)
The present paper is based on a research implemented with the second year students of Romance Philology, which took place in winter 2014/2015. Its purpose was to assess efficiency of b-learning used to improve the integration of lexical skills development with divergent thinking during our creative workshops. First of all, we provide the explanation of how the work on Moodle was planned. We then propose an analysis of the results of a survey carried out among our students to assess formal and functional level of their work on the platform. Finally, we share our reflections on the benefits, limitations and possible obstacles of the implementation of b-learning during a course, as well as some suggestions to optimize the objectives.